Porous alumina supported PA-Pd / g-C3N4 composite material as well as preparation method and application thereof
Through the preparation of porous alumina-supported Pd/g-C3N4 composite materials, the problem of narrow visible light response range and difficult recovery of g-C3N4-based photocatalytic materials is solved, and efficient organic wastewater treatment and material recycling are achieved.
Patent Information
- Application Number
- CN202411052968.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-20
AI Technical Summary
The existing g-C3N4-based photocatalytic materials have problems such as narrow visible light response range, high carrier recombination rate, weak conductivity, obvious agglomeration effect and inability to recover the powder state, which limits their application range and efficiency.
The porous alumina-loaded Pd/g-C3N4 composite material was used to prepare a porous hollow cylindrical structure through high-temperature calcination and ultrasonic dispersion, which improved the visible light response range of the material, reduced the carrier recombination rate, and enhanced the conductivity. And easy to recycle and recycle.
The photocatalytic reaction activity is improved, and the efficient organic wastewater treatment is achieved, with good stability and recycling, and it is suitable for the treatment needs of various organic wastewater.
Smart Images

Figure CN119158607A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water pollution control, and specifically relates to a method for synthesizing a macroscopic composite material PA@Pd / g-C3N4 of porous alumina (PA) loaded with Pd / g-C3N4 and applying the same to visible light catalytic degradation of pollutants in organic wastewater. Background Art
[0002] Water pollution, as a global environmental problem, is becoming increasingly serious, threatening the sustainable development of the ecosystem and human health. How to efficiently remove organic pollutants in water and purify sewage into recyclable water resources is crucial. Photocatalytic oxidation technology refers to the separation of photogenerated electrons and holes generated by semiconductor photocatalysts under the excitation of light, and the use of reactive oxygen species (ROS) such as hydroxyl radicals (·OH), superoxide radicals (·O 2 -) and photogenerated holes (h + ) and other treatment technologies for purifying pollutants. It has the advantages of mild reaction conditions, high efficiency, environmental friendliness, and renewable energy. It has shown great application potential in the field of water pollution control.
[0003] The application effect of this technology depends on the combined influence of factors such as light source intensity, solution pH value, catalyst (including type, crystal form, crystallinity, particle size, specific surface area), water quality, etc. Among them, the photocatalyst, as the core of the reaction, determines whether the reaction can proceed and whether it is efficient and thorough, and is the limiting factor of the reaction. Therefore, the key to realizing the practical application of photocatalysis is to prepare efficient photocatalysts. This requires first considering the absorption of sunlight by the catalyst. Since ultraviolet light below 400nm only accounts for about 5% of the total solar energy, the efficiency of ultraviolet light-responsive catalysts in utilizing solar energy is very limited. The development of visible light-responsive photocatalysts to utilize the energy of visible light, which accounts for about 43% of solar energy, is an inevitable trend for the large-scale application of photocatalytic materials.
[0004] In order to make the photocatalytic material have visible light catalytic activity, its bandgap width E gIt must be less than 3.0eV (corresponding to the incident light wavelength greater than 413nm). Graphitic carbon nitride (g-C3N4) is a typical two-dimensional non-metallic semiconductor. The π-conjugated sp2 hybrid structure in its structural unit gives it a suitable band gap width (2.7eV) and visible light absorption wavelength (460nm). At the same time, its preparation raw materials are easily available, the environmental content is abundant, the preparation cost is low, the thermal stability is high, and the chemical stability is good. Therefore, it is a very promising visible light catalytic material. However, studies have found that pure g-C3N4 still has some shortcomings when used as a photocatalytic material, mainly manifested as: narrow visible light response range (<450nm), high carrier recombination rate, weak conductivity, obvious agglomeration, etc. Therefore, improving the photocatalytic performance of g-C3N4 will help to expand its application range.
[0005] Doping with noble metals such as Pt, Pd, Au, and Ag is an effective way to improve the visible light photocatalytic activity of g-C3N4. First, g-C3N4 has a large specific surface area and rich N-containing functional groups. It can serve as an excellent noble metal carrier to disperse and stabilize nanoparticles. Secondly, noble metals have high photocatalytic activity and can enhance the capture of photons through the local surface plasmon resonance (SPR) effect, thereby improving the visible light absorption capacity of g-C3N4 and generating more photogenerated electron-hole pairs. In addition, the Schottky barrier formed between the noble metals and g-C3N4 can also inhibit the recombination of photogenerated electron-hole pairs. Pd is a common noble metal with high specific surface area, high stability, low toxicity, and efficient electron transfer characteristics. Pd nanoparticles loaded on the surface of the photocatalyst can often achieve higher photocatalytic efficiency than other noble metals. At the same time, Pd is relatively cheap, and the preparation of g-C3N4 visible light photocatalyst loaded with Pd has a high application prospect.
[0006] However, powdered g-C3N4-based photocatalysts are often faced with the problem of difficulty in recovery in practical applications, resulting in catalyst loss, secondary pollution, and pipeline blockage. The recovery and reuse of g-C3N4-based photocatalysts require immobilization measures. Its immobilization is mainly achieved by preparing magnetic composite materials, carbon-based composite materials, membrane materials, and other porous composite materials. Porous alumina (PA) is a non-toxic material with high surface area, large porosity, and high chemical stability, and is often used as an immobilized carrier for photocatalysts. Its three-dimensional porous structure can provide abundant reaction sites, improve the adsorption capacity and light capture capacity of the material, reduce the mass transfer and diffusion resistance of pollutants, and make the catalyst show significant activity. Its self-supporting macroscopic large-size structure can make the catalyst settle naturally after the reaction, which is convenient for the recovery and recycling of the catalyst. The design and construction of PA-loaded Pd / g-C3N4 visible light catalyst is of great significance and has broad application prospects.
[0007] In view of the above discussion, the present invention discloses a composite material of porous alumina loaded Pd / g-C3N4 and a preparation method and application thereof. Summary of the invention
[0008] The purpose of the present invention is to improve the photocatalytic performance and application range of g-C3N4 by providing a composite material of Pd / g-C3N4 loaded with porous alumina and its preparation method and application technology for the existing g-C3N4-based photocatalytic materials, such as narrow visible light response range, high carrier recombination rate, weak conductivity, obvious agglomeration, and inability to recycle powder. The material is used for photocatalytic oxidation treatment of pollutants in organic wastewater, and has obvious advantages such as strong catalytic activity, recyclability, easy separation and recovery; the wastewater treatment technology has the advantages of high treatment efficiency, rapid reaction, and wide pH adaptability.
[0009] The present invention is achieved through the following technical solutions.
[0010] The present invention provides a porous alumina-supported PA@Pd / g-C3N4 composite material, which contains six basic elements: C, H, O, N, Pd and Al. A single macroscopic body has the appearance of a porous hollow cylindrical body with an inner diameter of 0.9 to 1.2 cm, an outer diameter of 1.7 to 2.0 cm, a height of 1.8 to 2.2 cm and a mass of 2.7 to 3.6 g per body.
[0011] The present invention also provides a method for preparing the Pd / g-C3N4 composite material, the steps of which are as follows:
[0012] (1) a certain amount of urea is placed in a muffle furnace and calcined at high temperature, and then ground to obtain light yellow g-C3N4 powder;
[0013] (2) At room temperature, a certain amount of g-C3N4 aqueous solution was ultrasonically dispersed, a certain amount of PdCl2 aqueous solution acidified by 10% dilute hydrochloric acid was added, and a certain amount of NaBH4 solid was quickly added after stirring for 2 hours. After stirring for 12 hours, the mixture was centrifuged and washed to obtain Pd / g-C3N4 powder;
[0014] (3) A certain amount of 50% ethanol solution of Pd / g-C3N4 was slowly poured into a polyvinyl pyrrolidone (PVP) solution containing porous alumina (PA) macrobodies, and the solution was placed in a constant temperature oil bath and stirred for 15 min every 1 h. After 12 h, the solution was naturally cooled to room temperature, and the loosely loaded catalyst was removed by ultrasonic dispersion. The solution was then washed and dried to obtain PA@Pd / g-C3N4.
[0015] Furthermore, the high temperature calcination process in step (1) has a heating rate of 5°C·min -1 The temperature was raised to 550°C and maintained for 4 h, then naturally dropped to room temperature.
[0016] Furthermore, the mass concentration of the g-C3N4 aqueous solution in step (2) is 5 g / L, the mass concentration of PdCl2 in the PdCl2 aqueous solution acidified with hydrochloric acid is 1 g / L; the mass ratio of g-C3N4 to PdCl2 in the mixed solution is 50:1; the mass ratio of NaBH4 to PdCl2 in the mixed solution is 53.32:1; and the mass fraction of Pd atoms in the Pd / g-C3N4 is approximately 1%.
[0017] Furthermore, in step (3), the mass concentration of Pd / g-C3N4 in the ethanol solution of Pd / g-C3N4 is 1.2-2.4 g / L; the mass concentration of PA in the PVP solution containing PA is 300 g / L, and the mass concentration of PVP is 29-87 g / L; the volume ratio of the PVP solution containing PA to the ethanol solution containing Pd / g-C3N4 is 4:5; the mass ratio of PA macrosomes to Pd / g-C3N4 in the mixed solution is 100-200:1; and the temperature of the constant temperature oil bath is 100-140°C.
[0018] The present invention also provides the use of PA@Pd / g-C3N4 as a photocatalyst: the catalyst is used for visible light catalytic degradation of pollutants in organic wastewater to purify the wastewater.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) Compared with the existing g-C3N4-based photocatalyst, the PA@Pd / g-C3N4 provided by the present invention is used to treat organic wastewater. The visible light response range is improved, the carrier recombination rate is reduced, the conductivity is enhanced, and the photocatalytic reaction activity is higher.
[0021] (2) The PA@Pd / g-C3N4 provided by the present invention has high mechanical strength and good stability in water. Compared with the powdered g-C3N4-based photocatalyst, it does not agglomerate, is easy to separate and recover from water, and is convenient for recycling. Moreover, the photocatalytic performance of the catalyst does not decrease before and after PA immobilization, and is maintained well.
[0022] (3) The method for photocatalytic degradation of organic wastewater pollutants by PA@Pd / g-C3N4 provided by the present invention has high treatment efficiency, rapid reaction, and a wide adaptability to the initial pH range of wastewater, and is suitable for the treatment of various types of organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The visible light photocatalytic treatment effect of PA@Pd / g-C3N4 and comparative materials (PA@g-C3N4 and powdered Pd / g-C3N4) synthesized based on the method of Example 1 of the present invention on simulated tetracycline wastewater.
[0024] Figure 2 The visible light photocatalytic effect of PA@Pd / g-C3N4 material synthesized based on the method of Example 2 of the present invention on the simulated tetracycline wastewater.
[0025] Figure 3 The effect of the PA@Pd / g-C3N4 material synthesized based on the method of Example 3 of the present invention on the visible light catalytic treatment of simulated tetracycline wastewater.
[0026] Figure 4 The visible light photocatalytic treatment of PA@Pd / g-C3N4 material synthesized by preparation method 1 in Example 1 of the present invention simulates the recycling treatment effect of tetracycline wastewater.
[0027] Figure 5 This is the X-ray diffraction (XRD) spectrum of the PA@Pd / g-C3N4 material synthesized by method 1 of example of the present invention.
[0028] Figure 6 This is the Fourier transform infrared spectrum of the PA@Pd / g-C3N4 material synthesized by method 1 of embodiment of the present invention.
[0029] Figure 7 This is the visible-ultraviolet diffuse reflectance spectrum of the PA@Pd / g-C3N4 material synthesized by method 1 of example of the present invention.
[0030] Figure 8 This is the photoluminescence spectrum of the PA@Pd / g-C3N4 material synthesized by method 1 of example of the present invention.
[0031] Fig. 9 This is a photo of the appearance of the PA@Pd / g-C3N4 material synthesized by method 1 of example of the present invention. DETAILED DESCRIPTION
[0032] In order to better understand the contents of the present invention, the present invention is further described below in conjunction with examples and drawings, but the implementation methods of the present invention are not limited thereto, and the scope of protection claimed by the present invention is not limited to the scope represented by the examples.
[0033] Tetracycline (TC), as a highly representative antibiotic, is widely used in aquaculture, animal husbandry and the pharmaceutical industry, and has become a common new environmental pollutant. TC is difficult to be completely metabolized in animals. It is retained in the excrement and can enter the environmental water body through direct discharge, landfill, etc., which has an adverse effect on the ecosystem and human health. At present, traditional sewage treatment methods cannot effectively degrade TC in water, and it is necessary to develop new and effective treatment methods. The present invention selects TC simulated wastewater as the wastewater to be treated, and the degradation degree of TC represents the treatment efficiency of organic wastewater.
[0034] Example 1
[0035] A preparation method 1 of a porous alumina-loaded Pd / g-C3N4 composite material, the specific operation steps are as follows:
[0036] (1) Take a certain amount of urea and place it in a muffle furnace. Heat it to 550℃ at a rate of 5℃ / min at room temperature, calcine it for 4 hours, cool it to room temperature naturally, then take it out and grind it. Wash it with ultrapure water and anhydrous ethanol in turn, and dry it to obtain light yellow g-C3N4 powder.
[0037] (2) Disperse g-C3N4 powder in deionized water to obtain 5 g / L g-C3N4 dispersion, take 100 mL and add it to 10 mL 1 g / L 10% dilute hydrochloric acid acidified PdCl2 aqueous solution, stir for 2 h, then quickly add 0.5332 g NaBH4, stir and react for 12 h, centrifuge and wash the resulting precipitate, and dry to obtain Pd / g-C3N4 powder;
[0038] (3) Take 50mL of 1.2g / L Pd / g-C3N4 50% ethanol solution and slowly pour it into 40mL of polyvinyl pyrrolidone (PVP) solution containing 12g (4 pieces, about 3g / piece) porous alumina (PA) macro-bodies (PVP mass concentration is 29g / L), at which time the mass ratio of Pd / g-C3N4 to PA is 1:200. Place it in a 120℃ constant temperature oil bath and stir it for 15min every 1h. After 12h, it will naturally cool to room temperature, and remove the loose catalyst by ultrasonic dispersion, wash and dry it to obtain PA@Pd / g-C3N4.
[0039] A preparation method 2 of a porous alumina-loaded Pd / g-C3N4 composite material, which differs from the preparation method 1 in that the concentration of the Pd / g-C3N4 solution in step (3) is 2.4 g / L, and the mass ratio of Pd / g-C3N4 to PA is 1:100. The other steps are consistent with the method of the preparation method 1.
[0040] As control 1, a preparation method of a porous alumina-loaded g-C3N4 composite material PA@g-C3N4 is different from preparation method 1 in that step (2) is not performed, and when step (3) is performed, 50 ml of a 50% ethanol solution of 1.2 g / L g-C3N4 is poured into a PVP solution containing PA, and the other steps are consistent with the method of preparation method 1.
[0041] As control 2, a preparation method of a powdered Pd / g-C3N4 composite material is provided, which is different from preparation method 1 in that step (3) is not performed, and the other steps are consistent with those of preparation method 1.
[0042] Application of PA@Pd / g-C3N4 composite materials: The macroscopic PA@Pd / g-C3N4 prepared by preparation methods 1 and 2, the macroscopic PA@g-C3N4 of control group 1, and the powdered Pd / g-C3N4 of control group 2 were used as photocatalysts (the dosage of the macroscopic catalyst was 90 g / L (containing an equivalent of 0.45 g / L of Pd / g-C3N4), that is, 3 were added per 100 mL of the reaction system; the dosage of the powdered catalyst was 0.45 g / L), and the simulated tetracycline (TC) wastewater with an initial concentration of 10 mg / L was used as the wastewater to be treated. The wastewater treatment experiment was carried out in a photocatalytic device equipped with an HSX-UV3000 xenon lamp light source (350 W natural light with a 420 nm filter). The catalyst was added to the quartz reactor, stirred in a dark environment at room temperature for 30 minutes to complete the adsorption reaction, and samples were taken before the start and end of the reaction. After reaching the adsorption / desorption equilibrium, turn on the xenon light source, take samples at intervals after the photocatalytic reaction begins, and use an ultraviolet spectrophotometer to measure the remaining TC concentration in each water sample. The results are converted into removal rates. Figure 1 .
[0043] Figure 1 The results show that the powdered Pd / g-C3N4 has a certain adsorption capacity for the pollutant TC in the wastewater, and can adsorb and remove 19.9% of TC within 30 minutes. After 90 minutes of photocatalytic reaction, the terminal removal rate of TC is as high as 94.1%. After immobilization, the adsorption capacity of PA@Pd / g-C3N4 prepared by the two preparation methods for TC is improved, and the adsorption efficiency is about 41.7% to 48.0% within 30 minutes. After 90 minutes of visible light irradiation, the TC oxidation degradation efficiency can still be maintained at 94.0%, and when the mass ratio of Pd / g-C3N4 to PA changes in the range of 1:100 to 200, the performance of the photocatalyst is not much different. In contrast, the adsorption capacity of PA@g-C3N4 without Pd modification for TC is weak, and the adsorption efficiency within 30 minutes is only 7.3%. After 90 minutes of visible light irradiation, the removal rate of TC at the reaction end point is only 48.2%. It can be seen that the PA@Pd / g-C3N4 provided by this method has higher photocatalytic activity than PA@g-C3N4. And the photocatalytic performance of Pd / g-C3N4 after PA immobilization by this method is maintained well and does not decrease.
[0044] Example 2
[0045] A preparation method 3 of a porous alumina-loaded Pd / g-C3N4 composite material, the specific operation steps are as follows:
[0046] (1) Take a certain amount of urea and place it in a muffle furnace. Heat it to 550℃ at a rate of 5℃ / min at room temperature, calcine it for 4 hours, cool it to room temperature naturally, then take it out and grind it. Wash it with ultrapure water and anhydrous ethanol in turn, and dry it to obtain light yellow g-C3N4 powder.
[0047] (2) Disperse g-C3N4 powder in deionized water to obtain 5 g / L g-C3N4 dispersion, take 100 mL and add it to 10 mL 1 g / L 10% dilute hydrochloric acid acidified PdCl2 aqueous solution, stir for 2 h, then quickly add 0.5332 g NaBH4, stir and react for 12 h, centrifuge and wash the resulting precipitate, and dry to obtain Pd / g-C3N4 powder;
[0048] (3) Take 50mL of 1.2g / L Pd / g-C3N4 50% ethanol solution and slowly pour it into 40mL of polyvinyl pyrrolidone (PVP) solution containing 12g (4 pieces, about 3g / piece) porous alumina (PA) macro-bodies (PVP mass concentration is 29g / L). Place it in a 100℃ constant temperature oil bath and stir it for 15min every 1h. After 12h, it will naturally cool to room temperature. Ultrasonic dispersion is used to remove the loose catalyst, and then it is washed and dried to obtain PA@Pd / g-C3N4.
[0049] A preparation method 4 of a porous alumina-supported Pd / g-C3N4 composite material is different from the preparation method 3 in that in step (3), the temperature of the constant temperature oil bath is 140° C. The other steps are consistent with the method of the preparation method 3.
[0050] Application of PA@Pd / g-C3N4 composite material: The difference from Example 1 is that the photocatalysts are PA@Pd / g-C3N4 prepared by Preparation Method 1 of Example 1, Preparation Methods 3 and 4 of Example 2 (the dosage is 90 g / L, i.e., 3 are added per 100 mL of reaction system), and the other steps are the same as in Example 1. In the experiment, samples were taken at intervals before and after the pre-adsorption reaction and during the photocatalytic reaction, and the residual TC concentration in each water sample was determined by an ultraviolet spectrophotometer. Converted to removal rate, the results are shown in Figure 2 .
[0051] Figure 2 The results show that the removal efficiency of the pollutant TC in wastewater by PA@Pd / g-C3N4 prepared at different loading temperatures is slightly different. When the loading temperature is 120°C, the adsorption capacity of PA@Pd / g-C3N4 is the highest. Under visible light irradiation, TC is fully oxidized and degraded after 90 minutes. Although the final removal efficiency of TC is slightly reduced when the loading temperature is 100°C and 140°C, it can still reach more than 90.0%.
[0052] Example 3
[0053] A preparation method 5 of a porous alumina-loaded Pd / g-C3N4 composite material, the specific operation steps are as follows:
[0054] (1) Take a certain amount of urea and place it in a muffle furnace. Heat it to 550℃ at a rate of 5℃ / min at room temperature, calcine it for 4 hours, cool it to room temperature naturally, then take it out and grind it. Wash it with ultrapure water and anhydrous ethanol in turn, and dry it to obtain light yellow g-C3N4 powder.
[0055] (2) Disperse g-C3N4 powder in deionized water to obtain 5 g / L g-C3N4 dispersion, take 100 mL and add it to 10 mL 1 g / L 10% dilute hydrochloric acid acidified PdCl2 aqueous solution, stir for 2 h, then quickly add 0.5332 g NaBH4, stir and react for 12 h, centrifuge and wash the resulting precipitate, and dry to obtain Pd / g-C3N4 powder;
[0056] (3) Take 50mL of 1.2g / L Pd / g-C3N4 50% ethanol solution and slowly pour it into 40mL of polyvinyl pyrrolidone (PVP) solution containing 12g (4 pieces, about 3g / piece) porous alumina (PA) macro-bodies (PVP mass concentration is 58g / L). Place it in a 120℃ constant temperature oil bath and stir it for 15min every 1h. After 12h, it will naturally cool to room temperature. Ultrasonic dispersion is used to remove the loose catalyst, and then it is washed and dried to obtain PA@Pd / g-C3N4.
[0057] A preparation method 6 of a porous alumina-supported Pd / g-C3N4 composite material is different from the preparation method 5 in that in step (3), the mass concentration of PVP in the PVP solution is 87 g / L. The other steps are consistent with the method of the preparation method 5.
[0058] Application of PA@Pd / g-C3N4 composite material: The difference from Example 1 is that the photocatalyst is PA@Pd / g-C3N4 prepared by Preparation Method 1 of Example 1, Preparation Method 5 and Preparation Method 6 of Example 3, respectively, and the other steps are the same as those in Example 1. In the experiment, samples were taken at intervals before and after the pre-adsorption reaction and during the photocatalytic reaction, and the residual TC concentration in each water sample was determined by an ultraviolet spectrophotometer. The results are shown in Table 1. Figure 3 .
[0059] Figure 3 The results show that although the adsorption capacity of PA@Pd / g-C3N4 for TC is slightly reduced when the PVP mass concentration is 87 and 58 g / L, the PA@Pd / g-C3N4 prepared at three PVP concentrations can fully oxidize and degrade TC in wastewater under visible light irradiation within 90 minutes, and the removal rate reaches about 90%.
[0060] Example 4
[0061] Application of PA@Pd / g-C3N4 composite material: PA@Pd / g-C3N4 prepared in Example 1 was used as a photocatalyst, and the simulated tetracycline (TC) wastewater with an initial concentration of 10 mg / L was used as the wastewater to be treated. A wastewater recycling treatment experiment was carried out in a photocatalytic device equipped with an HSX-UV3000 xenon lamp light source (350W natural light with a 420nm filter). PA@Pd / g-C3N4 was added to the quartz reactor (the dosage was 90 g / L, i.e., 3 were added per 100 mL reaction system). After stirring for 30 minutes in a dark environment at room temperature to complete pre-adsorption, the xenon lamp light source was turned on. After the photocatalytic reaction was completed, PA@Pd / g-C3N4 was taken out, washed and dried, and the original reaction solution was dumped. This was a reaction cycle. A new 10 mg / L TC wastewater to be treated was prepared in the reactor, and a new round of pre-adsorption + photocatalytic reaction experiment was started. The cycle experiment was carried out 20 times in total. Sampling was performed at the end of each reaction cycle to determine the residual concentration of TC in the wastewater and convert it into removal rate. The results are shown in Figure 4 .
[0062] Figure 4 The results show that in 20 cycle experiments, the photodegradation removal efficiency of TC can be maintained above 94%, which fully demonstrates that PA@Pd / g-C3N4 has good photocatalytic stability and reusability.
[0063] The crystal structure of PA@Pd / g-C3N4 was characterized by X-ray diffraction. Figure 5 As shown. It can be seen that after Pd / g-C3N4 is loaded on the PA surface, its characteristic peak at 27.31° is still visible, but the peak intensity is significantly weaker than that of Pd / g-C3N4. The original characteristic peaks of PA at 19.44°, 37.59°, 39.47°, 45.84° and 67.00° corresponding to Y-Al2O3 disappear. This shows that the crystallinity of the catalyst is reduced after loading.
[0064] Fourier transform infrared spectroscopy was used to characterize the surface functional group structure of PA@Pd / g-C3N4. Figure 6 The results show that the characteristic peaks of PA@Pd / g-C3N4 have changed compared with the initial Pd / g-C3N4 and PA. -1 The newly appeared peaks in the range of 1190-1690 cm-1 represent the stretching vibrations of NH and OH. The widening of the peaks indicates the increase in the number of OH or NH2 groups on the catalyst surface. -1 In the range of 2000-3000 nm, the characteristic peak representing the stretching vibration of the triazine ring of Pd / g-C3N4 slowed down.-1 The characteristic peak at disappears, which may be due to the fact that part of the original active sites of Pd / g-C3N4 are occupied and covered during the loading process.
[0065] The optical response of PA@Pd / g-C3N4 was determined by UV-visible diffuse reflectance (UV-vis DRS) spectroscopy. Figure 7 As shown. PA@Pd / g-C3N4 has the ability to absorb light in the ultraviolet to visible range, and the absorption wavelength is about 450nm. Compared with the initial PA, due to the surface plasmon resonance effect of Pd, the absorption capacity of PA@Pd / g-C3N4 for visible light is enhanced, which is conducive to the generation of more photogenerated electron-hole pairs, thereby improving the photocatalytic performance of the catalyst.
[0066] Photoluminescence (PL) spectroscopy was used to characterize PA@Pd / g-C3N4 to verify the charge separation. Figure 8 It can be seen that the loading on PA changes the electronic structure of Pd / g-C3N4, causing the PL spectrum peak to red-shift from about 450nm to 500nm. At the same time, the spectrum peak intensity is significantly reduced, indicating that the photogenerated charge separation efficiency of the catalyst is enhanced.
[0067] Based on the above analysis, it can be seen that the PA@Pd / g-C3N4 provided by the present invention has enhanced visible light absorption ability, can generate sufficient photogenerated electron-hole pairs in the photocatalytic reaction, and has a high photogenerated charge separation efficiency. Therefore, it exhibits good photocatalyst performance and can effectively treat various types of organic wastewater.
[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A porous alumina-supported PA@Pd / g-C3N4 composite material, characterized in that: The composite material contains six basic elements, namely C, H, O, N, Pd and Al. A single macroscopic body has the appearance of a porous hollow cylinder with an inner diameter of 0.9 to 1.2 cm, an outer diameter of 1.7 to 2.0 cm, a height of 1.8 to 2.2 cm and a mass of 2.7 to 3.6 g per body.
2. A method for preparing a porous alumina-supported PA@Pd / g-C3N4 composite material, characterized in that: The following combination steps are included: Step (1) placing a certain amount of urea in a muffle furnace and calcining at high temperature, and grinding to obtain light yellow g-C3N4 powder; Step (2) at room temperature, taking a certain amount of g-C3N4 aqueous solution and dispersing it uniformly by ultrasonication, adding a certain amount of PdCl2 aqueous solution acidified by 10% dilute hydrochloric acid, stirring for 2 hours, and then quickly adding a certain amount of NaBH4 solid, stirring the reaction for 12 hours, and then centrifuging and washing to obtain Pd / g-C3N4 powder; Step (3) Take a certain amount of 50% ethanol solution of Pd / g-C3N4 and slowly pour it into the polyvinyl pyrrolidone (PVP) solution containing PA macrobodies, place it in a constant temperature oil bath and stir it for 15 minutes every 1 hour. After 12 hours, it naturally cools to room temperature, and ultrasonically disperses to remove the loosely loaded catalyst. The catalyst is washed and dried to obtain porous alumina-supported Pd / g-C3N4 (denoted as PA@Pd / g-C3N4).
3. The method for preparing a PA@Pd / g-C3N4 composite material according to claim 2, characterized in that: In step (1), the process parameters of the high temperature calcination process are: heating rate 5°C·min -1 The temperature was raised to 550°C and maintained for 4 h, then naturally dropped to room temperature.
4. The method for preparing a PA@Pd / g-C3N4 composite material according to claim 2, characterized in that: In step (2), the mass concentration of the g-C3N4 aqueous solution is 5 g / L, the mass concentration of PdCl2 in the PdCl2 aqueous solution acidified with hydrochloric acid is 1 g / L; the mass ratio of g-C3N4 to PdCl2 in the mixed solution is 50:1; the mass ratio of NaBH4 to PdCl2 in the mixed solution is 53.32:1; and the mass fraction of Pd atoms in the Pd / g-C3N4 is approximately 1%.
5. The method for preparing a PA@Pd / g-C3N4 composite material according to claim 2, characterized in that: In step (3), the mass concentration of Pd / g-C3N4 in the ethanol solution of Pd / g-C3N4 is 1.2-2.4 g / L; the mass concentration of PA in the PVP solution containing PA is 300 g / L, and the mass concentration of PVP is 29-87 g / L; the volume ratio of the PVP solution containing PA to the ethanol solution containing Pd / g-C3N4 is 4:5; the mass ratio of PA macrosomes to Pd / g-C3N4 in the mixed solution is 100-200:1; and the temperature of the constant temperature oil bath is 100-140°C.
6. A porous alumina-supported PA@Pd / g-C3N4 composite material, characterized in that: It is prepared according to the preparation method described in any one of claims 2 to 5.
7. Application of a composite material PA@Pd / g-C3N4 of porous alumina (PA) loaded with Pd / g-C3N4, characterized in that: Used for visible light catalytic degradation of pollutants in organic wastewater to purify the wastewater.
